The mother's care-giving role on children with intellectual disability - Tlale, Lloyd DN (Penerbit Universiti Kebangsaan Malaysia, 2019)
The mother's role in stimulating the child's intelligence is pivotal since she carries the pregnancy and the child spends more time with her than with the father in the first few years of life. The early years are crucial because it is the time for the child's rapid brain development. This paper examines the mother's role of care giving on children with intellectual disability in the early years. Qualitative focus group discussions were employed to collect data. Four focus group interviews. Two groups consisted of six participants and another two consisted of seven participants in each interviews. The findings revealed that not leading a healthy life may lead to children being born with intellectual disability. The mothers from a low socio-economic context thought that the child with intellectual disability was an excessive burden and craved that the child would die rather than live. They were not willing to consider treatment options unless the child would become completely normal. This paper recommends that the mothers as the only participants in this study limit the findings but provided first hand experiences connected to care-giving and children with intellectual disability. In addition, there is an implication that mothers of children with intellectual disabilities are at an obviously bigger risk of suffering from social disorder and dispossession as well as emotional suffering which can progress to severe depression.